KESULITAN BELAJAR PERKALIAN MATEMATIKA SISWA KELAS VI SD NEGERI 096 PEKANBARU - Meisye Wulandari; Jesi Alexander Alim (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
The main objective of this lesson is for students to master the concept of development, develop calculation skills, and understand the relevance of mathematics in everyday life. The learning of developmental arithmetic operations is an important part of developing students' understanding of basic mathematical concepts. The teacher has a central role in helping students understand arithmetic operations by providing systematic explanations, relating the concept of addition to real situations, and using interesting learning methods. This will assist students in building deep understanding and increase their involvement in learning. With the right efforts of teachers and students who are active in learning, it is hoped that learning mathematics arithmetic operations can run more effectively and students can achieve a good understanding of the concept.